Congenital retrosternal hernias of Morgagni: Manifestation and treatment in children - Oleksii Slepov; Sergii Kurinnyi; Oleksii Ponomarenko; Mikhailo Migur (Wolters Kluwer Medknow Publications, 2016)
Background: Due to scarcity of congenital diaphragmatic hearnias of Morgagni (CDHM), non-specific clinical presentation in the pediatric age group, we aimed to investigate the incidence, clinical manifestations, anatomical characteristics, and develop diagnostic algorithm and treatment of CDHM in children. Materials and Methods: The patients' records of children with CDHM treated in our hospital during past 20 years were retrospectively reviewed for the age at diagnosis, gender, clinical findings, anatomical features, operative details and outcome. Results: Since 1995 to 2014 we observed 6 (3 boys, 3 girls) patients with CDHM, that comprise 3.2% of all congenital diaphragmatic hernia cases (n = 185). Age at diagnosis varied from 3 mo. to 10y.o. Failure to thrive was main symptom in 4 patients, followed by recurrent respiratory infections (n = 3), dyspnea (n = 3), and gastrointestinal manifestations: constipation (n = 2), abdominal pain (n = 1). Work-up consisted of plain X-ray for all (n = 6), upper GI (n = 3), barium enema (n = 2), sonography (n = 6) and CT (n = 2). Abdominal approach used in 5 patients, and thoracotomy in one. Herniated contents were: liver lobes (n = 4), transverse colon (n = 3) and greater omentum (n = 1). 5 had right-sided lesion, 1- left-sided. Defect repaired using local tissues. Post-operative course was uneventful; all patients appeared well during follow-up. Conclusion: CDHM is very uncommon anomaly, very occasionally diagnosed at the early age. Failure to thrive and recurrent respiratory infections are most frequent clinical manifestations. In suspected CDHM we advocate the following work-up: plain chest and abdominal X-ray, contrast study (upper GI series or barium enema), ultrasonographic screen and CT scan. Surgical repair via abdominal approach, using local tissues and hernia sac removal is preferred.